RESOLUSI KONFLIK KEAGAMAAN INTEGRATIF: STUDI ATAS RESOLUSI KONFLIK SOSIAL KEAGAMAAN AMBON - Ismail, Roni (UIN Sunan Kalijaga Yogyakarta, 2020)
This article, that is a field research result, aims to analyze the conflict resolution adopted in resolving the 1999-2002 Ambon socio-religious conflict. It was found that the Ambon conflict resolution was done by integrative conflict resolution. Integrative conflict resolution is a conflict resolution model that integrates structural and cultural resolution together. Structural conflict resolution was pursued to resolve the roots of non-religious Ambon conflict, through: security approaches such as increasing 11,250 security personnel, upgrading Korem to Maluku Military Command, and enforcing civil emergency; the role of the Government in the Malino II Peace Agreement; Sharing of Muslim-Christian political leadership in the competition of the election of government local leaders; regents; and sharing of bureaucratic positions with SKJ. Meanwhile, the cultural conflict resolution is to resolve the roots of conflicts originated from religious issue, namely: the revitalization of multiculturalism by the state religious higher education of Ambon IAIN and IAKN; revitalizing the religion peaceful value through Christian-Muslim clerics through joint dialogue, cooperation, reconciliation, greetings, and deradicalization; optimizing the FKUB's role in life dialogue; and, the revitalization of the pela gandong between Muslim and Christian countries. Integrative conflict resolution is recognized by Ambonese Muslims and Christians as a very effective in resolving the roots of Ambon conflict, so that a firm foundation of peace is built in Ambon. In 2019, Ambon won a Harmony Award from the Indonesian Minister of Religion Affairs.